Interplay of Inflammatory Mediators with Epigenetics and Cartilage Modifications in Osteoarthritis - Raman, Swarna; FitzGerald, Una; Murphy, J. Mary (Frontiers in Bioengineering and Biotechnology, 2018)
Osteoarthritis (OA), a degenerative disease of diarthrodial joints, is influenced by mechanical and inflammatory factors with ageing, obesity, chronic injuries and secondary diseases thought to be major factors driving the process of articular cartilage degeneration. Chondrocytes, the cellular component of cartilage, reside in an avascular environment and normally have limited potential to replicate. However, extrinsic factors such as injury to the joint or intrinsic alterations to the chondrocytes themselves can lead to an altered phenotype and development of OA. Synovial inflammation is also a pivotal element of the osteoarthritic, degenerative process: influx of pro-inflammatory cytokines and production of matrix metalloproteinases accelerate advanced cellular processes such as synovitis and cartilage damage. As well as a genetic input, recent data has highlighted epigenetic factors as contributing to disease. Studies conducted over the last decade have focussed on three key aspects in OA; inflammation and the immune response, genome-wide association studies that have identified important genes undergoing epigenetic modifications and finally how chondrocytes transform in their function during development and disease. Data highlighted here has identified critical inflammatory genes involved in OA and how these factors impact chondrocyte hypertrophy in the disease. This review also addresses key inflammatory factors in synovial inflammation, epigenetics and chondrocyte fate and how agents that inhibit epigenetic mechanisms like DNA methylation and histone modifications could aid in development of long-term treatment strategies for the disease.